Perbedaan Hasil Belajar Kimia Siswa Berbantuan Peta Konsep dan Peta Pikiran Menggunakan CIRC - Hafni Indriati Nasution; Makharany Dalimunthe; Dian Yustika Rini Nasution (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2019)
This study aims to determine the differences in the chemistry learning outcomes of students taught with the help of media Concept Maps and Mind Maps using Cooperative Integrated Reading and Composition (CIRC) learning models on colloid subject matter. The population in this study is all students of class XI MIA SMA Swasta Nusantara Lubuk Pakam in the 2017/2018 school year consisting of 3 classes. The sample used in this study was taken by random sampling of two classes. The data analysis technique is a hypothesis test, namely the two-tail t-test. Based on the results of the data requirements test, it is known that the data from the pretest and posttest in the experimental class I and experiment II are normally distributed and homogeneous. Whereas to test the hypothesis on student learning outcomes (posttest) the price -thitung <-t½ α and tcount <t ½ α (-2,2181<-2,002 and 2,2181> 2,002) and are in the critical area, then Ho is rejected Ha accepted is that there are differences in chemistry learning outcomes of students who are taught with the help of media Concept Maps and Mind Maps using Cooperative Integrated Reading and Composition (CIRC) learning models on the subject matter of colloids.